PSYCHOLOGICAL COMPONENT OF MEDICAL REHABILITATION OF PATIENTS WITH POST-COVID SYNDROME (Conferencea, 2023)
The review article analyzes the results of research: scientific research on covid-19, which will allow premature identification of psychological problems (depression, anxiety, lack of motivation, etc.) that can serve as an obstacle to performing physical exercises, including breathing, necessary for secondary prevention of severe pulmonary complications. In China, more than half of the respondents rated the psychological impact as moderate, and about one-third reported moderate anxiety. Mental health problems were common in older Chinese adults (i.e., ≥55 years), with the prevalence of depressive symptoms reported to be 6% in this population [4].